A Glycoengineered Enzyme with Multiple Mannose-6-Phosphates Is Internalized into Diseased Cells to Restore Its Activity in Lysosomes. Issue 10 (18th October 2018) - Hyun, Ji Young; Kim, Sanggil; Lee, Hyun Soo; Shin, Injae
Summary: In this study we developed an efficient method to prepare glycoengineered β-N-acetylhexosaminidase containing multiple mannose-6-phosphates (M6Ps) by combining genetic code expansion with bioorthogonal ligation techniques. We found that multiple M6P-conjugated enzymes were produced with a high efficiency by using combined techniques. Importantly, glycoengineered enzymes entered lysosomes of patient-derived primary cells, which lack endogenous lysosomal β-N-acetylhexosaminidase, more readily than commercialized human β-hexosaminidase. Moreover, glycoengineered enzymes successfully removed GM2-ganglioside stored in lysosomes of diseased cells, indicating that its activity is restored in diseased cells. We also synthesized and applied a lysosome-targeting fluorogenic substrate to monitor endogenous and supplemental glycoengineered β-N-acetylhexosaminidase activities in lysosomes. The results of this study indicate that the present strategy, which relies on genetic code expansion and bioorthogonal ligation techniques, is highly attractive to generate multi-M6P-containing lysosomal enzymes that can be used to study lysosomal storage disorders associated with lysosomal enzyme deficiencies. Graphical Abstract: Highlights: The multi-M6P-containing lysosomal enzyme is prepared by using two techniques A glycoengineered enzyme is efficiently internalized into diseased cells A glycoengineered enzyme removes GM2-ganglioside stored in lysosomes of cells A lysosome-targeting fluorogenic substrate is prepared to monitor enzyme activity Abstract : A glycoengineered lysosomal enzyme containing multiple mannose-6-phosphates was prepared by combining genetic code expansion with bioorthogonal ligation techniques. The glycoengineered enzyme was efficiently internalized into diseased cells and accumulated into lysosomes. In addition, the enzyme successfully removed GM2-ganglioside stored in lysosomes of diseased cells.